1997
DOI: 10.1090/s0002-9939-97-04000-8
|View full text |Cite
|
Sign up to set email alerts
|

Statistical limit superior and limit inferior

Abstract: Abstract. Following the concept of statistical convergence and statistical cluster points of a sequence x, we give a definition of statistical limit superior and inferior which yields natural relationships among these ideas: e.g., x is statistically convergent if and only if st-liminfx = st-limsupx. The statistical core of x is also introduced, for which an analogue of Knopp's Core Theorem is proved. Also, it is proved that a bounded sequence that is C 1 -summable to its statistical limit superior is statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
98
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(99 citation statements)
references
References 20 publications
1
98
0
Order By: Relevance
“…In [21], we studied some relationships between convergence and uniform statistical convergence of a given sequence and its subsequences. The related notions of statistical limit superior and inferior and statistical cluster points have been studied in recent papers including [12,13] In the present paper, we are concerned with the relationships between the uniform statistical limit superior and inferior, almost convergence and uniform statistical convergence of a sequence. We also show some results about the set of uniform statistical cluster points of a given sequence and its subsequences and stretchings, including the discussion of the Lebesgue measure of the set of subsequences that retain the same set of uniform statistical cluster points.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [21], we studied some relationships between convergence and uniform statistical convergence of a given sequence and its subsequences. The related notions of statistical limit superior and inferior and statistical cluster points have been studied in recent papers including [12,13] In the present paper, we are concerned with the relationships between the uniform statistical limit superior and inferior, almost convergence and uniform statistical convergence of a sequence. We also show some results about the set of uniform statistical cluster points of a given sequence and its subsequences and stretchings, including the discussion of the Lebesgue measure of the set of subsequences that retain the same set of uniform statistical cluster points.…”
Section: Introductionmentioning
confidence: 99%
“…Orhan and Miller [18] have shown that if x almost converges to L , then the set of In [12], Fridy and Orhan introduced the definitions of the statistical limit superior and statistical limit inferior of a sequence and proved some results concerning these notions. Here we proceed analogously for the case of uniform statistical convergence.…”
Section: Introductionmentioning
confidence: 99%
“…(ii) C = (c nk ) ∈ (c : c λ ) reg if and only if (20) holds and (21), (22) also hold with α k = 0 for all k ∈ N and α = 1, respectively.…”
Section: λ-Corementioning
confidence: 99%
“…Let K be a subset of N. The natural density δ (K) of K ⊆ N is lim n→∞ n −1 {|{k ≤ n : k ∈ K}|} provided it exists, where |E| denotes the cardinality of the set E. A sequence x = (x k ) is called statistically convergent (st-convergent) to the number l if every ε > 0, δ ({k : |x k − l| ≥ ε}) = 0, [20] and is written as st − lim x = l. We write st and st 0 to denote the sets of all statistically convergent and statistically null sequences. The notion of the statistical core (or st-core) of a complex valued sequence has been introduced by Fridy and Orhan [21] and it is shown for a statistically bounded sequence x that st − core(x) = z∈C C x (z) for any x ∈ ∞ , where C x (z) = {w ∈ C : |w − z| ≤ st − lim sup k |x k − z|}.…”
Section: Introductionmentioning
confidence: 99%
“…Later on it was further investigated by Fridy and Orhan [4]. The idea depends on the notion of density of subset of  .…”
Section: Introductionmentioning
confidence: 99%